THE ROLE OF RELIGIOUS PRACTICES IN THE ADAPTATION AND SELF-DETERMINATION OF KYRGYZ YOUTH IN ISTANBUL (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Ethnographic research conducted in Istanbul allowed us to explore the role of religious practices on the adaptation of Kyrgyz youth to a new cultural and social environment. The issues of religious identity and adaptation of migrants become particularly relevant in the modern world in the context of globalisation and increased migration processes. This study aims to analyse how religious practices contribute to the integration of young people into Turkish society, while at the same time helping to preserve their national and cultural characteristics.
Keywords: migration, adaptation, religious practice, national identity, religious identity, kyrgyz youth.